Integrating digital twin technologies into the group design project for the Advanced Air Mobility Systems MSc course - Zhao, Junjie; Kallaka, Ruechuda; Conrad, Christopher; Gong, Tingyu; Xu, Yan; Tsourdos, Antonios (Elsevier, 2024)
This study aims to develop the content and material for the Group Design Project (GDP) with Digital Twin (DT) technologies, aligned with Future Flight Challenge (FFC) project deliveries involving Cranfield, the emerging Research and Development (R&D) capacities, and the increasing demands for talent and workforce from the industry. The GDP delivery and learning approach, structured as a five-phase process - project and technical management, Concept of Operations (ConOps) and requirements definition, system development, case study and evaluation, and final results - is stated in the paper. This proposed approach has been evaluated with the AAMS 23/24 academic year MSc GDP.
Keywords: 40 Engineering; 4007 Control Engineering, Mechatronics and Robotics; 4008 Electrical Engineering; Advanced air mobility systems; Group design project; Digital twin; MSc course; V Model